2008
DOI: 10.1002/mrd.20878
|View full text |Cite
|
Sign up to set email alerts
|

Effect of local neutralization of basic fibroblast growth factor or vascular endothelial growth factor by a specific antibody on the development of the corpus luteum in the cow

Abstract: Active angiogenesis and progesterone (P) synthesis occur in parallel during development of the corpus luteum (CL). Basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF) are known to stimulate angiogenesis and P synthesis in vitro. The aim of the present study was to investigate the impact of bFGF or VEGF on the CL development in the cow by using a specific antibody against bFGF or VEGF. bFGF antibody, VEGF antibody, or saline as a control (n = 4 cows/treatment) were injected direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 43 publications
5
57
1
5
Order By: Relevance
“…FGFs are potent mitogens for endothelial cells and other cell types, including luteal cells, and are therefore strong luteotropic factors within the CL (Yamashita et al 2008, Shirasuna et al 2010. The mechanisms that decrease FGF1 but increase FGF2 remain unknown; however, different expression levels of these luteotropic factors might have contributed to the incomplete luteolysis observed by Herzog et al (2012).…”
Section: Discussionmentioning
confidence: 99%
“…FGFs are potent mitogens for endothelial cells and other cell types, including luteal cells, and are therefore strong luteotropic factors within the CL (Yamashita et al 2008, Shirasuna et al 2010. The mechanisms that decrease FGF1 but increase FGF2 remain unknown; however, different expression levels of these luteotropic factors might have contributed to the incomplete luteolysis observed by Herzog et al (2012).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of VEGFA, FGF2 or PDGF action in vivo is associated with attenuated progesterone secretion resulting from changes in gross luteal structure, function and angiogenesis in the mouse, macaque and cow (Zimmermann et al 2001, Fraser et al 2005, Kuhnert et al 2008, Yamashita et al 2008. VEGFA and FGF2 stimulated progesterone release from microdialysed bovine early CL in vitro (Kobayashi et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that FGF2 protein levels are particularly high during the follicular-luteal transition, suggesting an important role for FGF2 during the development of the early bovine CL (Robinson et al 2007). Furthermore, injections of FGF2 antibody directly into the bovine CL decreased luteal volume and progesterone production (Yamashita et al 2008).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Zeleznik et al (1981) suggested that the selected follicles possess more elaborate microvasculature than other follicles. We concluded from studies in cow that vascular endothelial growth factor (VEGFA) and fibroblast growth factor 2 (FGF2) are involved in the proliferation of capillaries that accompany the selection of the preovulatory follicle resulting in an increased supply of nutrients, precursors and hormones, and therefore supporting the growth of the dominant follicle (Berisha et al 2000a, Yamashita et al 2008.…”
Section: Introductionmentioning
confidence: 99%